An insight into the sialotranscriptome and virome of Amazonian anophelines - Scarpassa, Vera Margarete; Debat, Humberto Julio; Alencar, Ronildo Baiatone; Ferreira Saraiva, José; Calvo, Eric; Arcà, Bruno; Ribeiro, José M. C. (BioMed Central, 2019)
Background: Saliva of mosquitoes contains anti-platelet, anti-clotting, vasodilatory, anti-complement and antiinflammatory substances that help the blood feeding process. The salivary polypeptides are at a fast pace of evolution possibly due to their relative lack of structural constraint and possibly also by positive selection on their genes leading to evasion of host immune pressure. Results: In this study, we used deep mRNA sequence to uncover for the first time the sialomes of four Amazonian anophelines species (Anopheles braziliensis, A. marajorara, A. nuneztovari and A. triannulatus) and extend the knowledge of the A. darlingi sialome. Two libraries were generated from A. darlingi mosquitoes, sampled from two localities separated ~ 1100 km apart. A total of 60,016 sequences were submitted to GenBank, which will help discovery of novel pharmacologically active polypeptides and the design of specific immunological markers of mosquito exposure. Additionally, in these analyses we identified and characterized novel phasmaviruses and anpheviruses associated to the sialomes of A. triannulatus, A. marajorara and A. darlingi species. Conclusions: Besides their pharmacological properties, which may be exploited for the development of new drugs (e.g. anti-thrombotics), salivary proteins of blood feeding arthropods may be turned into tools to prevent and/or better control vector borne diseases; for example, through the development of vaccines or biomarkers to evaluate human exposure to vector bites. The sialotranscriptome study reported here provided novel data on four New World anopheline species and allowed to extend our knowledge on the salivary repertoire of A. darlingi. Additionally, we discovered novel viruses following analysis of the transcriptomes, a procedure that should become standard within future RNAseq studies.